Situational Analysis of Conferences and Congresses Held in Tabriz University of Medical Sciences: 2005-2010 - Alireza Farajollahi; Abolghasem Amini; Mohammad Reza Rashidi; Abbas Shahbazi; Saber Azami-Aghdash (Tabriz University of Medical Sciences, 2014)
Introduction: Quality assessment of conferences and congresses and their performance seems inevitable due to the status and problems of holding them. Therefore, the aim of this study was the situational analysisof conferences and congresses held in Tabriz University of Medical Sciences during the years 2005-2010. Methods: In this descriptive study, five checklists were designed through literature review and panel meetings of experts to assess the quality and performance of conferences and congresses held in the University during the years 2005-2010. There were a total of 40 questions in the checklists extracted from the interviews of the responsible bodies. The data were analyzed using SPSS 19. Results: There were no statutory duties assigned to any of the committees. No indicator was used for selecting committee members. None of the conferences had been recalled at least a year prior. The university priorities had no role in organizing the conferences. Evaluation results were not available, and the conferences had very poor performance. Conclusion: Regarding the results of this study and the importance and costs of the scientific meetings, it is necessary to revise planning, poll-making and regular evaluation of these meetings to overcome weaknesses and improve the quality of the conferences and congress in the Tabriz University of Medical Sciences.